Real‐world safety and effectiveness of cenobamate in patients with focal onset seizures: Outcomes from an Expanded Access Program - Vicente Villanueva; Daniel Santos‐Carrasco; Pablo Cabezudo‐García; Asier Gómez‐Ibáñez; Mercedes Garcés; Pedro Serrano‐Castro; Maria D. Castro‐Vilanova; Débora Sayas; Francisco J. Lopez‐Gonzalez; Xiana Rodríguez‐Osorio; Gustavo Torres‐Gaona; Rosa A. Saiz‐Diaz; et al. (Epilepsia Open, 2023)
Abstract Objective This study investigated early, real‐world outcomes with cenobamate (CNB) in a large series of patients with highly drug‐resistant epilepsy within a Spanish Expanded Access Program (EAP). Method This was a multicenter, retrospective, observational study in 14 hospitals. Inclusion criteria were age ≥18 years, focal seizures, and EAP authorization. Data were sourced from patient clinical records. Primary effectiveness endpoints included reductions (100%, ≥90%, ≥75%, and ≥50%) or worsening in seizure frequency at 3‐, 6‐, and 12‐month visits and at the last visit. Safety endpoints included rates of adverse events (AEs) and AEs leading to discontinuation. Results The study included 170 patients. At baseline, median epilepsy duration was 26 years and median number of seizures/month was 11.3. The median number of prior antiseizure medications (ASMs) and concomitant ASMs were 12 and 3, respectively. Mean CNB dosages/day were 176 mg, 200 mg, and 250 mg at 3, 6, and 12 months. Retention rates were 98.2%, 94.5%, and 87% at 3, 6, and 12 months. At last available visit, the rate of seizure freedom was 13.3%; ≥90%, ≥75%, and ≥50% responder rates were 27.9%, 45.5%, and 63%, respectively. There was a significant reduction in the number of seizures per month (mean: 44.6%; median: 66.7%) between baseline and the last visit (P < 0.001). Responses were maintained regardless of the number of prior or concomitant ASMs. The number of concomitant ASMs was reduced in 44.7% of patients. The cumulative percentage of patients with AEs and AEs leading to discontinuation were 68.2% and 3.5% at 3 months, 74.1% and 4.1% at 6 months, and 74.1% and 4.1% at 12 months. The most frequent AEs were somnolence and dizziness. Significance In this highly refractory population, CNB showed a high response regardless of prior and concomitant ASMs. AEs were frequent but mostly mild‐to‐moderate, and few led to discontinuation.